John Scott correspondence - Scott, John, 1774-1827.
ALS written by Scott to R. Ballmanno regarding the completion of a portrait.
British engraver.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ballmanno, R. -- Correspondence; Engraving -- Great Britain; Artists